SOME CONSEQUENCES IN WEAK PROCESSES OF 3-GENERATION MIXING IN THE LEPTONIC SECTOR - Peres, OLG; PLEITEZ, V; Funchal, R. Z. (Amer Physical Soc, 1994)
We investigate the sensitivity of some weak processes to a Cabibbo-Kobayashi-Maskawa in the leptonic sector. Values for mixing angles and masses compatible with several experimental accelerator data were found. We discuss in this context neutrino oscillations and cosmological and astrophysical consequences as well.